The influence of gastronomic identity factors on food tourism development in the Republic of Serbia and Bosnia and Herzegovina - Kalenjuk Pivarski, Bojana; Paunić, Maja; Šarenac, Nemanja; Šmugović, Stefan; Mlinarević, Predrag; Ivanović, Velibor; Marjanović, Jelena; Pavlović, Stevan; Tekić, Dragana; Ðerčan, Bojan; Tešanović, Dragan; Gagić Jaraković, Snježana (Frontiers in Nutrition, 2024)
The gastronomic identity of an area is the key factor in tourism development, attracting numerous tourists and generating significant income. Numerous economic actors participate in its use and proper placement, and their perception of the gastronomic potential significantly affects its distribution and use in tourism. The main aim of this paper is to investigate the factors of gastronomic identity that influence the development of tourism, observed at two tourist destinations in Southeast Europe (the Republic of Serbia -RS, the city of Novi Sad with Fruška Gora Mountain, n = 305 and Bosnia and Herzegovina -BIH, the city of Sarajevo with Jahorina Mountain, n = 301).In order to define the factors that are relevant to food tourism development, a custommade GastroIdentity scale was created. A survey was conducted among employees in the hospitality and tourism industry, as well as employees in educational institutions in the field of hospitality and tourism.The research results show that employees from the RS area acknowledge the importance of organizing gastronomic events where local products are presented and that they understand that dishes and beverages with unique and recognizable tastes can characterize their area. Employees from the BIH area point out that the nutritional quality of their local agricultural and gastronomic products represents an advantage when compared to mass-produced ones, and that the local gastronomic culture and tradition are authentic representatives of the culture of the region.The GastroIdentity scale proved to be dependable, highlighting gastronomic culture and tradition as extremely crucial factors in tourism, using the input provided by the employees from the investigated areas. Noteworthy results were also recorded regarding the need for incentives for food tourism development in the investigated regions.